Occupation legal efforts by the community over land rights dispute of PT. Nusantara Plantation IV Regional II North Sumatra - Najwa Aisyah Fitri; Rahmat Ramadhani (Inspiring Law Journal, 2026)
Right to Use Business (HGU) is a land right granted by the state to a legal entity to cultivate state land within a certain period of time. In practice, the physical control of plantation land by the community (occupation) often causes legal conflicts, especially over land that is still burdened by HGU, as happened to PT. Nusantara Plantation IV Region II North Sumatra. This study aims to analyze the legal position of HGU holders, examine legal arrangements regarding plantation land occupation by the community, and identify legal remedies that can be taken in resolving these conflicts. This study uses an empirical legal method with a sociological juridical approach and is descriptive analytical. Data was obtained through literature studies and field research, including interviews with related parties, then analyzed qualitatively. The results of the study show that PT. The Nusantara IV Regional II North Sumatra Plantation has a legal status as an HGU holder as long as the right is still valid and used according to its designation. Occupation of plantation land without a valid basis of rights is an unlawful act that is contrary to agrarian laws and regulations. Legal remedies that can be carried out include non-litigation settlements through mediation and coordination with the government and the National Land Agency, as well as litigation settlement through the courts to obtain certainty and legal protection.